Abstraction and Empathy (Einfühlung) in Architecture: Rethinking Mosque Design in the Sancaklar Mosque - Şeyma Duman (Livenarch+ Journal)
This paper aims to explore the aesthetic theories of empathy (Einfühlung) and abstraction, focusing on their application to architectural works. Wilhelm Worringer’s psychological aesthetic theories serve as the framework for this study, particularly in analyzing how artistic styles reflect the internal world of the artist. The research examines how these theories have historically explained various art styles and their relevance to different cultures and epochs. The central focus is the Sancaklar Mosque, which serves as a case study for understanding how abstraction and empathy manifest in contemporary architecture. Through content analysis, the study identifies key concepts from Worringer’s “Abstraction and Empathy (Einfühlung)” and evaluates them against the physical and qualitative architectural elements of the mosque. The findings aim to contribute to the broader understanding of style in architecture, particularly through the lens of psychological aesthetics. This study offers a new and developable approach to analyzing architectural works by integrating these two important theories, demonstrating their significance in understanding architectural style across different historical and cultural contexts.